ANALISIS POTENSI BAHAYA DAN PENGENDALIAN MENGGUNAKAN METODE HIRARC PADA PERKEBUNAN KELAPA SAWIT PT FARINDA BERSAUDARA : ANALISIS POTENSI BAHAYA DAN PENGENDALIAN MENGGUNAKAN METODE HIRARC PADA PERKEBUNAN KELAPA SAWIT PT FARINDA BERSAUDARA - Abiyyu, Khairi (Fakultas Teknik Universitas Hamzanwadi, 2025)
Based on the work accident report data of PT. Farinda Bersaudara from 2022 to 2023, in the period 2022 there were 34 work accidents while in the period 2023 there were 36 work accidents, there was an increase in accidents from 2022 to 2023. So the researcher is interested in conducting research using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method, it is hoped that it can reduce or prevent work accidents that occur at PT. Farinda Bersaudara. Data collection is observation and interviews. Data analysis in this study, namely data processed using the HIRARC method, where this method includes hazard identification, risk assessment, and risk control. The results of the study of the potential hazards found at PT. Farinda siblings are mostly in the nursery work field with 22 potential hazards, then the harvester work field with 16 potential hazards, and the last is in the land clearing field with 15 potential hazards. Based on the risk assessment of the land clearing, nursery, and harvester work fields, the assessment categories are as follows: extreme 20%, high 17%, moderate 37% low 26%. The risk control hierarchy used in the land clearing, nursery, and harvester work fields includes elimination, substitution, engineering, administrative, and PPE.